Significados de la Identidad Personal a Partir del Uso de Redes Sociales como Instagram y Tik Tok en Adolescentes de la Ciudad de Floridablanca (2024)
The construction of this study is based on the research objective of analyzing the meanings that a group of adolescents from the city of Floridablanca construct about personal identity, based on the use of social networks such as Instagram and Tik Tok, which contributes to the reflection of the favorable and unfavorable of these social networks in the construction of their personal identity; In an interest to know what they perceive about social networks in their construction of personal identity, understanding that this interaction, so common nowadays, transcends in their formation as individuals, and social networks, without a clear criterion, can contribute to create a false identity distorting the real world. This study is within the qualitative approach to research, designed from phenomenology.